Control of an Arm-Hand Prosthesis by Mental Commands and Blinking - Varela Aldas, José; Castillo Salazar, David Ricardo; Borja Galeas, Carlos; Guevara Maldonado, César Byron; Arias Flores, Hugo Patricio; Fierro-Saltos, W.; Rivera, R.; Hidalgo-Guijarro, J.; Yandún-Velasteguí, M. (My University, 2020)
Patients who lack upper and lower extremities have difficulties in carrying out their daily activities. The new technological advances have allowed the development of robotic applications to support people with disabilities, also, portable electroencephalographic (EEG) sensors are increasingly accessible and allow the development of new proposals which involve the mental control of electronic systems. This work presents the control by mental orders of an arm-hand prosthesis using low-cost devices, the objective is to command the arm using the user’s attention and blinking, where the components are a brain signal sensor, a prosthesis, an Arduino board, six servomotors, and a computer. The developed program in Matlab allows controlling the arm by means of an attention level y blinking. The results show the functioning of the system through experimental tests and a usability test is applied, finally, the conclusions establish adequate coordination in the movements of the prosthesis and the patient indicate satisfaction with the proposal. © Springer Nature Switzerland AG 2020.
Keywords: Augmented reality; Design Thinking; Editorial design; User experience design